Phytochemical Profiling and Anticancer Potential of Praecitrullus fistulosus Fruit Extracts on Ehrlich Ascites Carcinoma (EAC) Cell Lines - Sharma, Rajesh; Annam, Vignesh; Tyagi, Nidhi; Kumar, Nitin (Journal of Neonatal Surgery, 2025)
The global incidence of cancer has prompted extensive research into finding novel, selective anticancer agents that target tumor cells while minimizing harm to normal cells. Traditional medicine, especially the use of plant-based compounds, has emerged as a promising source for discovering such therapeutic agents. This study investigates the potential anticancer activity of Praecitrullus fistulosus, a plant used in traditional medicine. The fruits of P. fistulosus were extracted using various solvents, including petroleum ether, chloroform, ethyl acetate, acetone, and ethanol, and were evaluated for their total phenolic and flavonoid contents. The ethanolic extract demonstrated the highest concentrations of both phenolic (24 mg/g) and flavonoid (21.28 mg/g) compounds. In vitro and in vivo assays were performed to assess the anticancer potential of these extracts. The in vivo study on Erlich Ascites Carcinoma (EAC) tumor-bearing mice showed a significant reduction in tumor volume, packed cell volume, and viable tumor cell count in treated groups, with the ethanol extract showing the most potent effect. The results suggest that the anticancer properties of P. fistulosus may be attributed to its high content of bioactive compounds, particularly polyphenolics and flavonoids, which likely exert both direct cytotoxic and antioxidant effects on tumor cells. This research highlights Praecitrullus fistulosus as a promising candidate for the development of novel anticancer therapies, warranting further investigation into its therapeutic potential.